Nível de aptidão física de idosas participantes de projeto social no município de Salinópolis-PA - SANTOS, Dennys Augusto da Fonseca dos (2019)
The processes/phases by which human beings pass through their existence are fundamental to any aspect associated with their way of living. His experience in different aspects may have consequences in the final phase of his life, as well as old age. During this phase of life the elderly tends to have a decrease in their organic functions, which favors functional loss, making difficult the simplest activities of daily living, and a more active routine can slow down these declines. In this sense, the objective of the present study is to analyze the indices of the variables components of the functional physical fitness of elderly women from the Social Project CIAMI (center for the integration of activities of the best age). The study is of a quantitative, descriptive nature and counted on a final sample of 11 elderly participants of the project that were subjected to evaluations of some component variables of functional physical fitness, pre and post 8 weeks of training. The study had as results the increase in the levels of strength resistance capacities, agility/dynamic balance after the training program. We conclude that the practice of physical exercises promotes positive influences on the functional physical fitness components of the elderly social projects participants and that a specific planning favors the practice of the physical education teacher and success in specific objectives associated with different components of the same.